P. 1
Integral Table

Integral Table

|Views: 4|Likes:
Published by Ibrahim Kahraman

More info:

Published by: Ibrahim Kahraman on Oct 27, 2011
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

06/19/2014

pdf

text

original

Table of Integrals∗

Basic Forms x dx = a+x x(a + x) − a ln √ x+ √ x+a (25) ln axdx = x ln ax − x √ 2 (−2b2 + abx + 3a2 x2 ) ax + b (26) 15a2 ln ax 1 dx = (ln ax)2 x 2 ln(ax + b)dx = 1 x(ax + b)dx = 3/2 (2ax + b) ax(ax + b) 4a √ (27) −b2 ln a x + a(ax + b) x+ b a ln(ax + b) − x, a = 0 (42) (43) Integrals with Logarithms

1 x dx = xn+1 n+1
n

(1) (2)

1 dx = ln x x udv = uv − vdu

√ x ax + bdx =

(3) (4)

(44)

1 1 dx = ln |ax + b| ax + b a Integrals of Rational Functions

ln(x2 + a2 ) dx = x ln(x2 + a2 ) + 2a tan−1

x − 2x (45) a

1 1 dx = − (x + a)2 x+a (x + a)n dx = (x + a)n+1 + c, n = −1 n+1 (x + a) ((n + 1)x − a) (n + 1)(n + 2)
n+1

(5) (6)

x3 (ax + b)dx =

b b2 x − 2 + x3 (ax + b) 12a 8a x 3 √ b3 + 5/2 ln a x + a(ax + b) (28) 8a

ln(x2 − a2 ) dx = x ln(x2 − a2 ) + a ln

x+a − 2x (46) x−a

ln ax2 + bx + c dx = − 2x +

1 a

2ax + b 4ac − b2 tan−1 √ 4ac − b2 (47)

x(x + a)n dx =

(7)

1 x2 ± a2 dx = x 2

1 x2 ± a2 ± a2 ln x + 2

x2 ± a2 (29)

b + x ln ax2 + bx + c 2a bx 1 − x2 2a 4 1 b2 + x2 − 2 2 a

1 dx = tan−1 x 1 + x2 1 1 x dx = tan−1 a2 + x2 a a x 1 dx = ln |a2 + x2 | a2 + x2 2 a2 x x dx = x − a tan−1 + x2 a
2

(8) (9) (10) x (11) (12) 1 x √ dx = sin−1 a a2 − x2 (13) x √ dx = x2 ± a2 x √ dx = − a2 − x2 x2 1 dx = x 2 ± a2 x2 ± a2 (33) a2 − x2 dx = 1 x 2 a2 − x2 + 1 2 x a tan−1 √ 2 a2 − x2 (30)
3/2

x ln(ax + b)dx =

ln(ax + b)

(48)

1 2 x2 ± a2 dx = x ± a2 3

(31)

x3 1 1 dx = x2 − a2 ln |a2 + x2 | 2 + x2 a 2 2 1 2 2ax + b dx = √ tan−1 √ ax2 + bx + c 4ac − b2 4ac − b2 1 1 a+x dx = ln , a=b (x + a)(x + b) b−a b+x x a dx = + ln |a + x| (x + a)2 a+x x 1 dx = ln |ax2 + bx + c| + bx + c 2a 2ax + b b − √ tan−1 √ a 4ac − b2 4ac − b2 Integrals with Roots √ 2 x − adx = (x − a)3/2 3 √ 1 √ dx = 2 x ± a x±a √ √ 1 dx = −2 a − x a−x

1 √ dx = ln x + x2 ± a2

1 x ln a2 − b2 x2 dx = − x2 + 2 1 a2 x2 − 2 2 b

ln a2 − b2 x2

(49)

x2 ± a2

(32) Integrals with Exponentials 1 ax e a

eax dx = (34) √

(50)

xeax dx =

(14)

a2 − x2

(35)

√ √ 1 √ ax i π xe + 3/2 erf i ax , a 2a x 2 2 where erf(x) = √ e−t dt π 0 xex dx = (x − 1)ex

(51)

(15) √

x2

x2 ± a2

1 2 a ln x + 2

x2 ± a2 (36)

(52) eax (53) (54) (55) (56) (57)

ax2

xeax dx =

x 1 − 2 a a

(16)

ax2 + bx + cdx = +

b + 2ax 4a

ax2 + bx + c a(ax2 + bx+ c) (37)

x2 ex dx = x2 − 2x + 2 ex x2 eax dx = x2 2x 2 − 2 + 3 a a a eax

4ac − b2 ln 2ax + b + 2 8a3/2

(17) x (18) (19) √ 1 ax2 + bx + c = 2 a 48a5/2
2 2

x3 ex dx = x3 − 3x2 + 6x − 6 ex ax2 + bx + c xn eax dx = ax2 + bx + x (38) xn eax dx = xn eax n − a a xn−1 eax dx

− 3b + 2abx + 8a(c + ax ) √ +3(b3 − 4abc) ln b + 2ax + 2 a

(−1)n Γ[1 + n, −ax], an+1

√ 2 2 x x − adx = a(x − a)3/2 + (x − a)5/2 3 5 √ ax + bdx = 2b 2x + 3a 3 √ ax + b

(58)

(20)

1 1 √ dx = √ ln 2ax + b + 2 a ax2 + bx + c

where Γ(a, x) = a(ax2 + bx + c) (39)
x

ta−1 e−t dt

(21) (22) (23) x 1 √ dx = ax2 + bx + c a ax2 + bx + c b − 3/2 ln 2ax + b + 2 a(ax2 + bx + c) 2a dx x = √ + x2 )3/2 a2 a2 + x2

(ax + b)3/2 dx = √

2 (ax + b)5/2 5a √ 2a) x ± a

√ √ 2 i π eax dx = − √ erf ix a 2 a √ √ 2 π e−ax dx = √ erf x a 2 a xe−ax dx = −
2

(59) (60) (61)

2 x dx = (x 3 x±a

(40)

1 −ax2 e 2a

2010. From http://integral-table.com, last revised July 31, 2011. This material is provided as is without warranty or representation about the accuracy, correctness or suitability of this material for any purpose. This work is licensed under the Creative Commons Attribution-Noncommercial-No Derivative Works 3.0 United States License. To view a copy of this license, visit http://creativecommons.org/licenses/by-nc-nd/3.0/us/ or send a letter to Creative Commons, 171 Second Street, Suite 300, San Francisco, California, 94105, USA.

«

x dx = − a−x

x(a − x) − a tan

−1

x(a − x) x−a

(24)

(a2

(41)

x2 e−ax dx =

2

1 4

√ π x −ax2 erf(x a) − e a3 2a

(62)

ix)] (74) xn cosaxdx = a = b (114) a=b (115) (97) cos2 ax sin axdx = − 1 cos3 ax 3a (75) 1 (ia)1−n [(−1)n Γ(n + 1.a = b 2(a − b) 2(a + b) (71) x cos xdx = cos x + x sin x x cos axdx = 1 x cos ax + sin ax a2 a (93) (94) (95) sin[(2a − b)x] sin ax cos bxdx = − 4(2a − b) sin[(2a + b)x] sin bx − + 2b 4(2a + b) 2 x2 cos xdx = 2x cos x + x2 − 2 sin x (72) 2x cos ax a2 x2 − 2 x cos axdx = + sin ax 2 a a3 2 eax sinh bxdx =  ax  e  2 [−b cosh bx + a sinh bx] a − b2 2ax x e  − 4a 2 eax tanh bxdx =  (a+2b)x e a a 2bx    (a + 2b) 2 F1 1 + 2b . . −ix) − (−1)n Γ(n + 1. 2 + 2b . . −e   a 1 . 1E. −e2bx − eax 2 F1  a −1 ax 2b  ax   e − 2 tan [e ]   a tanh ax dx = 1 ln cosh ax a a=b (113) a=b sin2 x cos xdx = 1 sin3 x 3 (96) (73) cos[(2a − b)x] cos bx cos ax sin bxdx = − 4(2a − b) 2b cos[(2a + b)x] − 4(2a + b) 2 1 xn cosxdx = − (i)n+1 [Γ(n + 1. n = 0 n (65) x = ln | csc x − cot x| + C csc xdx = ln tan 2 1 csc axdx = − cot ax a 2 (109) sin3 axdx = − (66) (67) (68) Integrals of Hyperbolic Functions (89) cosh axdx = 1 1 csc3 xdx = − cot x csc x + ln | csc x − cot x| 2 2 1 csc x cot xdx = − cscn x. 1. . ixa)] (98) cos ax cosh bxdx = sin2 ax cos2 bxdx = sin[2(a − b)x] x sin 2ax − − 4 8a 16(a − b) sin[2(a + b)x] sin 2bx + − (76) 8b 16(a + b) sin 4ax x − 8 32a (77) 1 [a sin ax cosh bx a2 + b2 +b cos ax sinh bx] (116) x sin xdx = −x cos x + sin x x sin axdx = − sin ax x cos ax + a a2 (99) (100) cos ax sinh bxdx = 1 [b cos ax cosh bx+ a2 + b2 a sin ax sinh bx] (117) sin2 ax cos2 axdx = 1 tan axdx = − ln cos ax a tan2 axdx = −x + 1 tan ax a x2 sin xdx = 2 − x2 cos x + 2x sin x (78) (79) x2 sin axdx = 2−a x 2x sin ax cos ax + a3 a2 2 2 (101) sin ax cosh bxdx = (102) 1 [−a cos ax cosh bx+ a2 + b2 b sin ax sinh bx] (118) tann axdx = 2 F1 tann+1 ax × a(1 + n) n+3 n+1 . 1. −ix)] 2 (103) Products of Trigonometric Functions and Exponentials sin ax sinh bxdx = 1 [b cosh bx sin ax− a2 + b2 a cos ax sinh bx] (119) tan3 axdx = (81) sinh ax cosh axdx = (82) ex sin xdx = 1 x e (sin x − cos x) 2 (104) sinh ax cosh bxdx = 1 [−2ax + sinh 2ax] 4a (120) sec xdx = ln | sec x + tan x| = 2 tanh−1 tan sec2 axdx = 1 tan ax a (83) ebx sin axdx = 1 ebx (b sin ax − a cos ax) a2 + b2 (105) 1 [b cosh bx sinh ax b2 − a2 −a cosh ax sinh bx] (121) . . 1. −ix) 2 +(−1)n Γ(n + 1. − tan2 ax 2 2 1 1 ln cos ax + sec2 ax a 2a x 2 (80) 1 xn sin xdx = − (i)n [Γ(n + 1. . cos2 ax 2 2 2 3 sin ax sin 3ax + 4a 12a (91) (92) a=b (111) a=b (112) (69) sec x csc xdx = ln | tan x| Products of Trigonometric Functions and Monomials cos3 axdx = (70) cos ax sin bxdx = cos[(a − b)x] cos[(a + b)x] − . −iax) 2 −Γ(n + 1. cos2 ax 2 2 2 3 cos ax cos 3ax + 4a 12a 1 sin ax a 1 sec x tan xdx = secn x. n = 0 n n cos axdx = sin 2ax x cos2 axdx = + 2 4a cosp axdx = − 2 F1 1 sinh ax a (110) (90) eax cosh bxdx =  ax  e  2 [a cosh bx − b sinh bx] a − b2 2ax x e  + 4a 2 sinh axdx = 1 cosh ax a 1 cos1+p ax× a(1 + p) 1+p 1 3+p .Integrals with Trigonometric Functions sec3 x dx = 1 sin axdx = − cos ax a sin2 axdx = x sin 2ax − 2 4a (63) sec x tan xdx = sec x (64) sec2 x tan xdx = sin axdx = 1 − cos ax a 2 F1 n n 1 1 sec x tan x + ln | sec x + tan x| 2 2 (84) ex cos xdx = 1 x e (sin x + cos x) 2 (106) (85) (86) ebx cos axdx = 1 ebx (a sin ax + b cos ax) a2 + b2 1 x e (cos x − x cos x + x sin x) 2 1 x e (x cos x − sin x + x sin x) 2 (107) 1 sec2 x 2 xex sin xdx = (87) xex cos xdx = (88) (108) 1 1−n 3 .

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->